![image](https://tex.z-dn.net/?f=a_n%3D4n-7%3B%5C%5C%0Aa_1-%3F%3B%5C%5C%0Ad-%3F%3B%5C%5C%0Aa_%7B13%7D-%3F%3B%5C%5C%0Aa_%7Bn%2B1%7D%3Da_n%2Bd%3D%3D%3Ed%3Da_%7Bn%2B1%7D-a_%7Bn%7D%3D4%28n%2B1%29-7-4n%3D%5C%5C%0A%3D4n%2B4-4n%3D4%3B%5C%5C%0Ad%3D4%3B%5C%5C%0Aa_1%3D4%5Ccdot1-7%3D4-7%3D-3%3B%5C%5C%0Aa_%7B13%7D%3Da_1%2B%28n-1%29%5Ccdot+d%3D-3%2B%2813-1%29%5Ccdot4%3D-3%2B12%5Ccdot4%3D-3%2B48%3D45%3B%5C%5C%0Aa_%7B13%7D%3D4%5Ccdot13-7%3D52-7%3D13%3B%5C%5C%0A)
d=a_{n+1}-a_{n}=4(n+1)-7-4n=\\
=4n+4-4n=4;\\
d=4;\\
a_1=4\cdot1-7=4-7=-3;\\
a_{13}=a_1+(n-1)\cdot d=-3+(13-1)\cdot4=-3+12\cdot4=-3+48=45;\\
a_{13}=4\cdot13-7=52-7=13;\\
" alt="a_n=4n-7;\\
a_1-?;\\
d-?;\\
a_{13}-?;\\
a_{n+1}=a_n+d==>d=a_{n+1}-a_{n}=4(n+1)-7-4n=\\
=4n+4-4n=4;\\
d=4;\\
a_1=4\cdot1-7=4-7=-3;\\
a_{13}=a_1+(n-1)\cdot d=-3+(13-1)\cdot4=-3+12\cdot4=-3+48=45;\\
a_{13}=4\cdot13-7=52-7=13;\\
" align="absmiddle" class="latex-formula">
ответ